Gluteal Tendon Repair Augmented with a Synthetic Ligament: Surgical Technique and a Case Series. Issue 2 (March 2014) - Bucher, Thomas A.; Darcy, Peter; Ebert, Jay R.; Smith, Anne; Janes, Greg
We describe an augmented surgical repair technique for gluteus minimus and medius tears, along with a supportive case series. A consecutive series of 22 patients presenting with clinical and radiological findings consistent with hip abductor tears, who had undergone failed prior conservative treatments, were prospectively recruited. Patients underwent open bursectomy, Y-iliotibial release, debridement of the diseased tendon, decortication of the trochanteric foot-plate and reattachment augmented with a LARS ligament through a trans-osseous tunnel, together with suture anchors. All patients were assessed pre- and postoperatively to 12 months with the Oxford Hip Score (OHS), the Short-Form Health Survey (SF-36) and a Visual Analogue Pain Scale (VAS), while a satisfaction scale was employed at 12 months. A statistically significant improvement (p≤0.05) was observed for all patient reported outcome measures, while all patients were at least 'satisfied' with the procedure at 12 months. One patient reported some lateral hip discomfort at 10 months, and removal of the LARS interference screw provided immediate relief. One patient had a urological catheter-related complication. With no other complications and no clinical failures of the repair, we believe the technique to be safe and reliable, whilst reducing the incidence of re-tears as reported in the existing literature.